Phone skills for the information age - Maxwell, Dorothy (McGraw-Hill, 2006)
This five-hour program teaches proper phone use to help students develop and maintain professional relationships, project a positive company image, and provide reliable service. Phone Skills for the Information Age features realistic situations and problems found in today's increasingly complex business environments. The text includes reinforcement exercises, self-assessments, case studies, reference charts for on-the-job use, and a glossary.